(untitled) (Proceedings of the International Conference on Social Sciences, 2018)
Satisfying customer need is a key to obtain sustainable competitive advantage in the business world. Due to high competitiveness in Sri Lankan private higher education industry “Student Satisfaction” is a crucial success factor for institutes to remain in the industry. Therefore there is a growing need to understand factors that affect satisfaction of students of private sector higher educational institutes. This study empirically examines factors affecting student satisfaction of Business Management undergraduates’ of a leading Sri Lankan private higher educational institute. Previous research done under various environments has recommended a variety of factors affecting user satisfaction. This study developed a model which adopted recognition of the programme, quality of the teaching and academic administration from HEDPERF model of Firdaus (2005) with two other dimensions facilities and skill match taken from other studies. The study was conducted in correlation with UN Sustainable Development Agenda – 2030 (Aim No-4 <<The High Quality of Education). A survey questionnaire was conducted to investigate the critical factors affecting student’s satisfaction. The collected data was analyzed using SPSS. The data analysis categorized under two main statistical techniques such as, “Descriptive Statistics” & “Inferential Statistics”. The relationship between all the five independent variables and overall student satisfactions were tested using bivariate analysis. Further this study also tries to answer if there any differences in perception of satisfaction in terms demographic variables such as gender and level of study semester. The results highlighted that recognition of the programme and academic administration are the critical factors affecting overall student satisfaction. The results also showed that there were no differences in perception in terms of gender and level of study semester.